Cervicovaginal cytology, HPV testing and vaginal flora in transmasculine persons receiving testosterone. Issue 11 (8th August 2022) - Lin, Lawrence Hsu; Zhou, Fang; Elishaev, Esther; Khader, Samer; Hernandez, Andrea; Marcus, Alan; Adler, Esther
Abstract: Background: Testosterone is one of the strategies that transmasculine persons can elect in order to align physical traits to their gender identity. Previous studies have shown morphologic changes in the genital tract associated with testosterone. Here, we aim to evaluate cervicovaginal cytology specimens (Pap tests) and high‐risk HPV (HR‐HPV) testing from transmasculine individuals receiving testosterone. Methods: This is a retrospective cohort of 61 transmasculine individuals receiving testosterone from 2013 to 2021. Cytologic diagnoses from 65 Pap tests were correlated with HPV status and histologic follow‐up and compared with the institutional data and a cohort of cisgender women with atrophic changes. Results: The median age was 28 years and median time of testosterone use was 3 years. Transmasculine persons showed significantly higher rates of HSIL (2%) and unsatisfactory (16%) when compared with the institutional data and atrophic cohort of cisgender women. After reviewing slides of 46 cases, additional findings were noted: atrophy was present in 87%, glycogenated cells were seen in 30%, and Lactobacilli were substantially decreased in 89%. Among 32 available HPV tests, 19% were positive for HR‐HPV and 81% were negative. On histologic follow‐up, all HR‐HPV‐positive cases with abnormal cytology showed HSIL, while none of the HPV‐negative cases revealed HSIL. Conclusion: Our study cohort demonstrated a high percentage of abnormal Pap tests in transmasculine persons receiving testosterone. Testosterone seems to induce changes in squamous cells and shifts in vaginal flora. HR‐HPV testing can be a useful adjunct in the workup of abnormal Pap tests from transmasculine individuals.